2014
DOI: 10.1093/jxb/eru102
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of an mvp mutant reveals important changes in global gene expression and a role for methyl jasmonate in vernalization and flowering in wheat

Abstract: Summary Molecular and physiological analyses of a wheat mvp mutant, and winter and spring wheats suggest that methyl jasmonate is involved in modulating vernalization and floral transition in wheat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 75 publications
2
36
0
Order By: Relevance
“…Arabidopsis plants treated with jasmonate are also late flowering with short internodes and loss of apical dominance, giving an appearance similar to bop1-6D or pny pnf/+ mutants. Inhibitory effects of MeJA on flowering are also reported in Pharbitis nil (Maciejewska and Kopceiwicz, 2002;Maciejewska et al, 2004), Chenopodium rubrum (Albrechtová and Ullmann, 1994), and einkorn wheat (Triticum monococcum; Diallo et al, 2014). JA antagonism of growth or flowering has been linked to repression of GA biosynthesis (Magome et al, 2004;Heinrich et al, 2013), stabilization of DELLAs (Yang et al, 2012), and/or induction of AP2/ERF factors (Magome et al, 2008;Sun et al, 2008;Kang et al, 2011;Licausi et al, 2013).…”
Section: Ja Antagonism Of Growth and Floweringmentioning
confidence: 95%
See 1 more Smart Citation
“…Arabidopsis plants treated with jasmonate are also late flowering with short internodes and loss of apical dominance, giving an appearance similar to bop1-6D or pny pnf/+ mutants. Inhibitory effects of MeJA on flowering are also reported in Pharbitis nil (Maciejewska and Kopceiwicz, 2002;Maciejewska et al, 2004), Chenopodium rubrum (Albrechtová and Ullmann, 1994), and einkorn wheat (Triticum monococcum; Diallo et al, 2014). JA antagonism of growth or flowering has been linked to repression of GA biosynthesis (Magome et al, 2004;Heinrich et al, 2013), stabilization of DELLAs (Yang et al, 2012), and/or induction of AP2/ERF factors (Magome et al, 2008;Sun et al, 2008;Kang et al, 2011;Licausi et al, 2013).…”
Section: Ja Antagonism Of Growth and Floweringmentioning
confidence: 95%
“…Its targets include SPL genes, which are also directly activated by SOC1 and FD Porri et al, 2012). How these various pathways are integrated with stress signals is an area of active study (Yang et al, 2012;Heinrich et al, 2013;Hou et al, 2013;Diallo et al, 2014;Stief et al, 2014).…”
mentioning
confidence: 99%
“…Conversely, MeJA levels were maintained high till 4DAS, while these levels returned to control levels at 8DAS. The results indicates that the two different forms of JAs are presumably interchangeable and might share common signal transduction pathway in Pongamia during salt stress (Diallo et al, 2014; Mitra Baldwin, 2014; Cao et al, 2016; Li et al, 2017). An exogenous application of JAs reduced shoot growth, enhanced water uptake and cell wall synthesis in certain crop species (Kang et al, 2005; Uddin et al, 2013; Shahzad et al, 2015; Tavallali Karimi, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…jasmonic acid-amido synthetase JAR1 (JAR1) is one of 19 closely related Arabidopsis genes that issimilar to the auxin-induced soybean GH3 gene [59]. Methyl JA (MeJA)-treated vernalization in insensitive spring wheat exhibited flowering and considerably downregulated TaVRN1 and TaFT1 genes, suggesting that MeJA may modulate vernalization and flowering time in wheat [60]. Previous studies have reported that CK promotes the formation of floral meristems and exogenously applied CK promotes Arabidopsis flowering [61,62].…”
Section: Changes In the Plant Hormone Signal Transduction Pathway Durmentioning
confidence: 99%